BDP/FF NEXThaler to Improve Asthma Control Status in the Real World: The NEWTON Study - Braido F; Arnaboldi E; Barile S; Cavalieri L; Ingrassia E; Russo M; Piraino A (Journal of Asthma and Allergy, 2023)
Fulvio Braido,1,2 Enrico Arnaboldi,1,2 Sara Barile,3 Luca Cavalieri,4 Eleonora Ingrassia,4 Maria Russo,1,2 Alessio Piraino4 1Respiratory Unit for Continuity of Care, IRCCS, Ospedale Policlinico San Martino, Genova, Italy; 2Department of Internal Medicine (DiMI), University of Genova, Genova, Italy; 3Chiesi Farmaceutici S.p.A., Parma, Italy; 4Chiesi Italia S.p.A ., Parma, ItalyCorrespondence: Fulvio Braido, Respiratory Unit for Continuity of Care, IRCCS, Ospedale Policlinico San Martino, Genova, Italy, Email fulvio.braido@unige.itAbstract: In this article, we discuss the importance of real-world data in the treatment of patients with asthma and specifically the role of maintenance and reliever therapy (MART) with beclometasone dipropionate (BDP)/formoterol fumarate dihydrate (FF) delivered through a dry-powder inhaler (DPI) that contains an extrafine formulation. We also present the design of the NEWTON study. This multinational, multicenter, prospective, observational study will evaluate the real-world use of extrafine BDP/FF via a DPI as maintenance therapy and MART in patients with moderate to severe asthma. The study’s primary outcome will be the proportion of patients improving their asthma control. Digitally collected patient-reported outcomes, such as the 5-item Asthma Control Questionnaire, the EuroQol 5-dimension 5-level, and the Test of the Adherence to Inhalers, will be used to assess the patient’s asthma control, quality of life, and treatment adherence. Moreover, a new patient-reported outcome, the “Speed of change in health feeling” questionnaire, will be validated in a subgroup of patients. Overall, the results of this study will provide a real-life assessment of patients who perceived clinical benefits in a large cohort of asthmatics in Europe treated as per current clinical practice.Keywords: asthma, dry-powder inhaler, beclometasone dipropionate/formoterol fumarate, observational study